2022
DOI: 10.3389/fncel.2022.932572
|View full text |Cite
|
Sign up to set email alerts
|

All roads lead to heterogeneity: The complex involvement of astrocytes and microglia in the pathogenesis of Alzheimer’s disease

Abstract: In recent years, glial cells have been acknowledged as key players in the pathogenesis of Alzheimer’s disease (AD), a neurodegenerative condition in which an accumulation of intracellular neurofibrillary tangles and extracellular fibrillar amyloid beta is notably observed in the central nervous system. Genome-wide association studies have shown, both in microglia and astrocytes, an increase in gene variants associated with a higher risk of developing late-onset AD. Microglia, the resident innate immune cells o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 204 publications
(231 reference statements)
0
7
0
Order By: Relevance
“…To add more complexity, studies in AD mouse models and human post-mortem tissue from AD patients showed that microglia may play distinct roles depending on disease stage and spatial distribution in the brain. 15 Microglia have ramified processes that allow them to survey their surroundings, a state called ramified or surveying micoglia. 16 Environmental triggers such as cellular debris or pathogens induce microglia activation and transformation into an ameboid state with a large, round cell body.…”
Section: The Role Of Neuroinflammation For Ad Pathologymentioning
confidence: 99%
See 3 more Smart Citations
“…To add more complexity, studies in AD mouse models and human post-mortem tissue from AD patients showed that microglia may play distinct roles depending on disease stage and spatial distribution in the brain. 15 Microglia have ramified processes that allow them to survey their surroundings, a state called ramified or surveying micoglia. 16 Environmental triggers such as cellular debris or pathogens induce microglia activation and transformation into an ameboid state with a large, round cell body.…”
Section: The Role Of Neuroinflammation For Ad Pathologymentioning
confidence: 99%
“… 18 Various other microglial states have been described, including (1) hypertrophic microglia (large cell bodies with short and thick processes) in aged patients with AD with Braak stage IV-VI, (2) dystrophic or senescent microglia (with spherical swellings in their processes, lipofuscin deposits, and positive staining for L-ferritin) predominantly near tau pathology in AD human brain, and (3) dark microglia (with ramified dark processes due to accumulation of markers indicating oxidative stress, e.g., dilated endoplasmic reticulum and altered mitochondria) near axon terminals and dendritic spines in brains of 14-month-old APP/PS1 mice (AD mouse model expressing chimeric human/mouse APP and mutant PSEN1). 15 In addition to the phenotypic heterogeneity, microglia in AD are characterized by a vast heterogeneity of genetic signatures and cytokine expression profiles. Genome-wide association studies identified triggered receptor expressed on myeloid cells ( Trem2 ) as a crucial driver of microglial activation and appearance of disease-associated microglia (DAM) in AD.…”
Section: The Role Of Neuroinflammation For Ad Pathologymentioning
confidence: 99%
See 2 more Smart Citations
“…Alterations of the cannabinoid system are associated with the inflammatory processes of these conditions, but intriguingly, are also implicated in the alterations in affect which may co-occur (Vecchiarelli et al, 2021). Non-neuronal cells in the central nervous system are in particular related to the pathogenesis, maintenance and/or alleviation of neuroinflammatory, neurodegenerative and pain states (Kelly et al, 2020;Šimončičová et al, 2022;St-Pierre et al, 2022). To further elucidate the role of cannabinoids in these disease contexts, this Research Topic includes a collection of primary research articles and a mini review on the role of cannabinoids in these states in particular in non-neuronal cells.Two primary research articles in the collection investigate the role of enzymes that metabolize N-acylethanolamines, including the primary endocannabinoid, Narachidonoylethanolamine (anandamide or AEA).…”
mentioning
confidence: 99%